Effect of different vegetation restoration patterns on community structure and co-occurrence networks of soil fungi in the karst region - Zou, Xiaoxiao; Yao, Kai; Zeng, Zhaoxia; Zeng, Fuping; Lu, Lihong; Zhang, Hao (Frontiers in Plant Science, 2024)
Introduction: The Grain for Green Project (GGP) by the Chinese government was an important vegetation restoration project in ecologically fragile and severely degraded karst regions. Soil fungi play a facilitating role in the cycling of nutrients both above and below the ground. , which is crucial for maintaining ecosystem function and stability. In karst regions, their role is particularly critical due to the unique geological and soil characteristics, as they mitigate soil erosion, enhance soil fertility, and promote vegetation growth. However, little is known about how the implementation of this project shifts the co-occurrence network topological features and assembly processes of karst soil fungi, which limits our further understanding of karst vegetation restoration.Methods: We By usinged MiSeq high-throughput sequencing combined with null model analysis technology, we detected community diversity, composition, cooccurrence networks, and assembly mechanisms of soil fungi under three GGP patterns (crop, grassland, and plantation) in the southwestern karst region.Results: Ascomycota and Basidiomycota were the main fungal phyla in all the karst soils. Returning crop to plantation and grassland had no significant effect on α diversity of soil fungi (p P > 0.05), but did significantly affect the β diversity (p P = 0.001). Soil moisture and total nitrogen (TN) were the main factors affecting the community structure of soil fungi. Compared with crop, soil fungi networks in grassland and plantation exhibited a higher nodes, edges, degree, and relatively larger network size, indicating that vegetation restoration enhanced fungal interactions. The soil fungi networks in grassland and plantation were more connected than those in crop, implying that the interaction between species was further strengthened after returning the crop to plantation and grassland. In addition, null-model analysis showed that the assembly process of soil fungal communities from crop to grassland and plantation shifted from an undominant process to dispersal limitation. Discussion: These data indicated that GGP in karst region changed the composition and assembly mechanisms of the soil fungal community and enhanced the interaction between fungal species, which can contribute to a better understanding of the fungal mechanisms involved in the restoration of degraded karst soils through vegetation recovery.